From Product to Relationship: A Service-Dominant Logic Approach to Gen Z Loyalty in Kopitiams - Setiadi, Deni; Rohman, Fatchur; Hapsari, Raditha Dwi Vata (Universitas Brawijaya, Indonesia, 2025)
The rapid proliferation of the coffee shop industry, coupled with the high mobility and exploratory nature of Generation Z students, presents a critical challenge for Kopitiam businesses in maintaining customer retention. Grounded in Service-Dominant Logic (SDL), this study aims to analyze the influence of personalized experience and food and beverage quality on customer loyalty, with brand trust serving as a mediating variable. This explanatory quantitative research collected data through a purposive sampling technique from 150 Generation Z university students in Malang City who had visited a Kopitiam at least twice within the last six months. Data were analyzed using Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The findings reveal a distinct dichotomy where personalized experience has a significant direct effect on enhancing customer loyalty, whereas food and beverage quality does not directly influence loyalty but is fully mediated by brand trust. This indicates that in a saturated market, product quality functions merely as a hygiene factor, while brand trust acts as the pivotal psychological axis for Generation Z customer commitment. The novelty of this study lies in positioning brand trust as a bridge between functional product value and relational experience within the Kopitiam cultural ecosystem. These findings imply that Kopitiam operators must shift their focus from mere menu innovation to